Practices of communication among administrators in college Dar Al-Hikmah Kajang : students' perceptions - Seri Atikah (Kulliyyah of Education, International Islamic University Malaysia, 2019)
Communication plays a most important role in all aspects of human life and is especially significant in an educational organisation. The purpose of this study is to examine the practices of communication that occurs between administrators and students in College Dar Al-Hikmah Kajang from the students' perception. It further aims to determine the significant differences of students' perception on the communication skills of administrators based on various demographic variables and to identify the communication barriers faced by international students in the said college. The mathematical theory of communication by Shannon and Weaver (1949) was used to guide the research. This study employs a quantitative research method and SPSS version 22.0 to analyse the data. A total of 200 students in College Dar Al-Hikmah participated in this study. The main results obtained show that administrators have a moderate level of verbal communication in terms of face-to-face and written communication as perceived by students. The college administrators also have a high level of nonverbal communication skills in terms of using tone of voice and listening skills. In addition, there was no significant difference in the students' perception on the verbal communication and nonverbal communication skills of administrators based on their gender, level of study, and nationality. Finally, language is the most prominent communication barrier faced by international students in College Dar Al-Hikmah, Kajang